Confirmatory factor analysis of the internet addiction test in university students. - Coelho, Manuela de Mendonça Figueirêdo; Cavalcante, Viviane Mamede Vasconcelos; Castro, Tifanny Horta; Oriá, Mônica Oliveira Batista; Beserra, Eveline Pinheiro; Gubert, Fabiane do Amaral; Martins, Mariana Cavalcante; Marques, Marília Braga; Nogueira, Paula Sacha Frota; Coutinho, Janaína Fonseca Victor; Barbosa, Rachel Gabriel Bastos (Revista Cuidarte)
Introduction: The Internet Addiction Test is a psychometric instrument designed to assess and quantify the severity of internet addiction and explore aspects of internet misuse. Objective: To confirm the factorial validity of the Internet Addiction Test in a sample of university students. Materials and Methods: A methodological study was conducted with 5,292 Brazilian university students. The data underwent confirmatory factor analysis and internal consistency assessment. Results: The Kaiser-Meyer-Olkin test yielded a value of 0.946, indicating that the sample was adequate. Factor analysis confirmed the existence of factors that fully align with the original American scale. The model showed satisfactory fit indices, including a Comparative Fit Index of 0.978, Tucker-Lewis Index of 0.976, Standardized Root Mean Residual of 0.053, and Root Mean Square Error of Approximation of 0.054 [0.052-0.056], which are consistent with previously established satisfactory fit criteria. Factor loadings of the items were considered high, ranging from 0.43 (item I7) to 0.89 (item I17). Discussion: The Internet Addiction Test's six-factor structure was validated, which is identical to that proposed by the original American version and was consistent with other studies that have also identified the same multifactorial structure of the original instrument. Therefore, psychiatric nurses can confidently use it when caring for young university students. Conclusion: The Internet Addiction Test is a valid and reliable instrument for measuring internet addiction among university students and can be used by mental health nurses to identify such issues.